Implementation of PBL-flipped classroom learning model to improve the learning outcomes of junior high school students in human excretion system materials - Lyta Adela Rossely; Mohammad Budiyanto; Aris Rudi Purnomo (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to describe the increase in learning outcomes and student responses by applying the PBL-Flipped Classroom learning model in human excretion system materials. The type of research used is pre-experimental design research through one group pretest-postest design. The subjects in this study were involved as a class VIII-D at Junior High School 1 Tugu. The data collection technique was carried out using a knowledge test in the form of multiple choice questions before and after the PBL-Flipped Classroom learning model was applied and student response questionnaires to the application of the PBL-Flipped Learning model. The data analysis technique used is descriptive quantitative. The results of the data obtained were then analyzed in the form of student learning outcomes and student responses. The increase in student learning outcomes can be seen from the N-Gain analysis and paired sample t-test. The increase in student learning outcomes can be seen from the N-Gain analysis and paired sample t-test. The results of the N-Gain test obtained were 0.66, which was included in the medium category. Student learning outcomes have increased significantly, with a significance value of 0.00 < 0.05. The results of the student response were included in the very good category with a percentage of 99%. Based on the facts above, there is an effect of the PBL-Flipped Classroom learning model to improve the learning outcomes of junior high school students on the human excretion system materials.